2017
DOI: 10.5430/jnep.v7n9p67
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of perceived genetic-genomic knowledge of nurse educators and graduate degree nursing students

Abstract: Objective and rationale: Comparison of self-perceived genetic-genomic knowledge of nurse educators and graduate degree nursing students enrolled at a large diverse urban university in the US. Comfort level in performing genetic-genomic related tasks and its perceived relevance to nursing also explored. Practicing clinicians are expected to have Genetics and Genomics (G-G) knowledge to provide care to a client and their family with a genetic condition and faculty expected to be able to educate these practitione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 34 publications
(66 reference statements)
0
20
0
5
Order By: Relevance
“…Genetically-based healthcare is a worldwide consideration, yet considerable evidence has shown that nurses overall lack confidence and competency in this area, and dispensing genomic education is erratic and variable. [25][26][27] Genomics relevance is correlated to health overall, including risks and indicators of disease, therapeutic actions and decisions, advancement of new therapies, and responses to treatment interventions. [1] Nurses need to be confident in their ability to comprehend this science, advocate, elucidate information, support and educate patients and their families through their lifespan.…”
Section: Simulationmentioning
confidence: 99%
“…Genetically-based healthcare is a worldwide consideration, yet considerable evidence has shown that nurses overall lack confidence and competency in this area, and dispensing genomic education is erratic and variable. [25][26][27] Genomics relevance is correlated to health overall, including risks and indicators of disease, therapeutic actions and decisions, advancement of new therapies, and responses to treatment interventions. [1] Nurses need to be confident in their ability to comprehend this science, advocate, elucidate information, support and educate patients and their families through their lifespan.…”
Section: Simulationmentioning
confidence: 99%
“…[12] The adapted survey, Genetics/Genomics Literacy Assessment (GGLA), included concepts related to perceptions and attitudes about genetics incorporation into nursing programs and comfort level in practice and education, and was previously utilized to further explore nurse educators' and advanced degree nursing students. [12,15] Nurses' fundamental self-confidence and comfort in genomic related accountabilities continues to be minimal. [16] Having students rate their knowledge, attitude and comfort level of genomics demonstrated findings that expressed minimal to moderate knowledge as well as comfort levels, while expressing the need to know this knowledge as a practicing nurse.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies exploring nurse faculty and practicing nurses' foundational preparedness to implement genomic content has demonstrated minimal to moderate foundational knowledge and comfort levels. [15,[20][21][22][23][24][25][26] There is a genomic knowledge deficit correlating to a dearth in nurse educators' confidence to assimilate and disseminate genomic gen. [27] Nursing faculty are required to prepare students for practice which includes the integration of genomic understanding and its application to practice, thus, knowledge and confidence in this content is a prerequisite. [19] The continued relevance of genomic knowledge translation to clinical practice requires practicing nurses' incorporating and promoting personalized efficient and effective nursing care.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations